Explaining Obesity- and Smoking-related Healthcare Costs through Unconditional Quantile Regression - Bijan Borah; James Naessens; Kerry Olsen; Nilay Shah (Journal of Health Economics and Outcomes Research)
**Background:** This paper assesses obesity- and smoking-related incremental healthcare costs for the employees and dependents of a large U.S. employer.